Співвідношення системи права та системи законодавства - Галюк, Р. Г.; Galjuk, R. (Одеса : Юрид. л-ра, 2014)
The problem of the relation of law and the system of legislation is relevant because very often there is a substitution of concepts. So, despite the fact that the system of law and a legal system are similar in meaning to the concept, they have significant differences.
Галюк Р. Г. Співвідношення системи права та системи законодавства / Р. Г. Галюк // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 129-134.
Keywords: система права; система законодавства; держава; галузь права; система законодательства; государство; отрасль права; system of law; legal system; state; branch of law